ANTIMICROBIAL ACTIVITY OF ESSENTIAL OILS OF PHYSALIS ANGULATA. L - Osho, A; Adetunji, T.; Fayemi, S. O.; Moronkola, D. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The need for a reduction in drug resistance led to the investigation of Argemone Mexicana L. as an agent against Bacillus subtilis, Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, Candida stellatoidea and Candida torulopsis, using well diffusion and minimum inhibitory concentrations methods. The sensitivity of Bacillus Subtilis, Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus to the essential oils of both the aerial and root parts were determined. Pseudomonas aeruginosa was resistant to the essential oil from both the aerial and root part of the plant. C. torulopsis, C. stellatoidea and C. albicans were susceptible to the essential oils from the aerial and root part of the plant. The minimum inhibitory concentrations ranging between 3.75mg/ml and 4.0mg/ml were recorded for Bacillus subtilis, Klebsiella pneumoniae by the aerial and the root extracts, but P. aeruginosa and S. aureus were not susceptible to the aerial and root extracts. The observed inhibition of selected bacteria and fungi by oils of Physalis angulata makes it a promising antimicrobial agent. This study justifies its uses for treatment of sores, cuts, intestinal and digestive problems and some skin-diseases often reported in folkloric medicine.